Ameliorative Effects of Supplemental Nutrition on Growth and Essential Oil Yield of Saline Irrigated Satureja montana. Issue 5 (3rd September 2019) - Hegazy, Mona H.; Sabra, Ali S.; Alharbi, Basmah M.; Said-Al Ahl, Hussein A.H.; Astatkie, Tess; Grulova, Daniela; Abdelrazik, Tamer M.
Abstract: In this present study, the response of Satureja montana plant to tap water (0.4 dS/m) and saline water irrigation (4 dS/m) treatments (NaCl, NaCl+CaCl2, NaCl+Na2 SO4, NaCl+(NH4 )2 SO4, NaCl+CaCl2 +Na2 SO4, NaCl+CaCl2 +(NH4 )2 SO4, NaCl+Na2 SO4 +(NH4)2 SO4, and NaCl+CaCl2 +Na2 SO4 +(NH4)2 SO4 ) was observed. The results showed significant effects of saline water on growth, essential oil content and yield and proline accumulation of the plant. As compared to tap water, saline water irrigation decreased plant height, number of branches, fresh and dry weights of herb, essential oil content and yield, but increased proline content. Among the saline irrigation treatments, the highest proline and the lowest plant height, number of branches, fresh and dry weights of herb, essential oil content and yield were recorded in NaCl alone. The results revealed that the reduction in growth and essential oil content and yield due to saline stress was alleviated by the addition of Ca 2+, NH4 +, and SO4 . The chemical composition analysis showed that carvacrol, camphor, m-cymene, β-phellandrene and γ-terpinene were the major compounds of the essential oil. The highest carvacrol (68.1 %) was obtained from plants irrigated with NaCl+CaCl2 +(NH4 )2 SO4 . However, plants irrigated with tap water gave higher β-phellandrene (12.6 %) and camphor (43.4 %). NaCl treatment gave higher m-cymene (14.1%); and higher γ-terpinene(12.2 %) was obtained from the NaCl+CaCl2 treatment. Based on these results, it can be concluded that application of NaCl with Ca 2+, NH4 +, and SO4 alone or mixed can lessen the harmful effects of NaCl. Therefore, the application of Ca 2+, NH4 +, and SO4 is recommended to increase salt stress tolerance of Satureja montana .